Establishment of a reverse transcription–recombinase polymerase amplification–lateral flow dipstick method for the dual detection of Israeli acute paralysis virus and chronic bee paralysis virus - Sun, Li; Cheng, Yu; Fei, Dongliang; Ma, Yueyu; Ma, Mingxiao; Li, Ming (Frontiers in Microbiology, 2024)
As an important social insect, honey bees play crucial roles in agricultural production, sustainable development of agricultural production, and the balance of the natural environment. However, in recent years, Israeli acute paralysis virus (IAPV) and chronic bee paralysis virus (CBPV), the main pathogens of bee paralysis, have continuously harmed bee colonies and caused certain losses to the beekeeping industry. Some beekeeping farms are located in wild or remote mountainous areas, and samples from these farms cannot be sent to the laboratory for testing in a timely manner, thereby limiting the accurate and rapid diagnosis of the disease. In this study, we used a reverse transcription-recombinase polymerase amplification-lateral flow dipstick (RT-RPA-LFD) method for the dual detection of IAPV and CBPV. RPA primers and LFD detection probes were designed separately for their conserved genes. Primers and probes were screened, and the forward and reverse primer ratios, reaction times, and temperatures were optimized. According to the results of the optimization tests, the optimal reaction temperature for RT-RPA is 37°C , and when combined with LFD, detection with the naked eye requires <20 min. The developed RPA-LFD method specifically targets IAPV and CBPV and has no cross-reactivity with other common bee viruses. In addition, the minimum detection limit of the RT-RPA-LFD method is 10 1 copies/μL. Based this study, this method is suitable for the detection of clinical samples and can be used for field detection of IAPV and CBPV.